Loads of continuous mechanics for uprighting the second molar on the second molar and premolar - Shibasaki, Wendel Minoro Muniz [UNESP]; Martins, Renato Parsekian [UNESP] (Elsevier, 2021)
Introduction: This paper aims to evaluate the effect of tube height on uprighting a mandibular second molar with a continuous arch, specifically the main effects on the molar tube and the side effects on the second premolar bracket. Methods: Slot brackets (0.18-in) and tubes were passively bonded from the left second molar to the right second premolar of the patient's cast and fixed to an orthodontic force tester. A mesially tipped second molar along with its tube was positioned at 5 different heights in relation to the bracket slots of the remaining appliance: 2 mm below (group −2), 1 mm below (group −1), leveled (group 0), 1 mm above (group 1) and 2 mm above (group 2). Each group had 10 different 0.016 × 0.022-in superelastic nickel-titanium wires tied one at a time to the appliance to register the vertical forces (Fz) and tipping moments (Mx) produced at the molar tube and the premolar bracket, statistically. Analysis of variance was used to identify differences of load among the groups for wire response to the position of the tube in relation to the other brackets’ slots. Results: As the molar tube was positioned more occlusally, Fz and Mx decreased at the molar tube from 1.31 N to 0.75 N and 13.98 N.mm to 11.84 N.mm, respectively, whereas at the premolar bracket, Fz and Mx decreased from 1.52 N to 0.88 N and 8.77 N.mm to 1.05 N.mm, respectively. Conclusions: In all groups, the load system at the molar tube (the main effects) registered a distal tipping moment and an extrusive force, whereas at the premolar bracket, the load system (side effects) included a distal tipping moment and an intrusive force. As the tube moved occlusally, the extrusive force and the uprighting moment decreased, along with the side effects at the premolar bracket. Attempting to bond the molar tube more occlusally (within reasonable intraoral dimensions) when trying to upright a molar does not appear to be sufficient to keep a molar from extruding.